Stress and Satisfaction attained by retirees through bridge employment in service sector (International Journal of Scientific Research and Management (IJSRM), 2017)
Old age is an inevitable and universal phenomenon of human life because ageing is a natural process. Ageing is more often a process of mental attitude rather than physical changes in the body. Old age is associated with “Retirement”. Retirement is one of the most significant events in an individual’s life which influences his/her psycho – social status. It can be defined as the complete withdrawal from employment along with entitlement to income that is based on having been employed over a period of years.